2019
DOI: 10.1093/ibd/izz084
|View full text |Cite
|
Sign up to set email alerts
|

Adalimumab or Infliximab for the Prevention of Early Postoperative Recurrence of Crohn Disease: Results From the ENEIDA Registry

Abstract: Background Anti–tumor necrosis factor agents (anti-TNFs) are efficacious at preventing the postoperative recurrence (POR) of Crohn disease, as demonstrated in 2 randomized controlled trials. However, real-life data for infliximab or adalimumab in this setting are scarce. Our aim was to assess both the efficiency of anti-TNFs at preventing early POR of Crohn disease in clinical practice and the associated risk factors for POR. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 38 publications
5
16
0
Order By: Relevance
“… 160 Findings from this registry demonstrate that infliximab and adalimumab have similar efficacy for the prevention of postoperative recurrence, and that findings were consistent with results obtained in randomized controlled trials. 160 …”
Section: Effects Of Tnf Inhibitors On Patients With Intestinal Stricture and Postoperative Recurrence After Ileocaecal Resectionsupporting
confidence: 80%
“… 160 Findings from this registry demonstrate that infliximab and adalimumab have similar efficacy for the prevention of postoperative recurrence, and that findings were consistent with results obtained in randomized controlled trials. 160 …”
Section: Effects Of Tnf Inhibitors On Patients With Intestinal Stricture and Postoperative Recurrence After Ileocaecal Resectionsupporting
confidence: 80%
“…In our meta‐analysis, most of the included studies used infliximab (n = 9), while six used adalimumab and eight used both infliximab and adalimumab. While there was a significant difference in the rate of recurrence, one study reported real life observational data on the efficacy of anti‐TNF‐α agents at preventing the POR of CD and did not find significant differences in endoscopic POR between patients treated with infliximab or adalimumab at 18 months (40% vs 30%, P = 0.2) 24 . Similar observations have been made on the MULTIPER 28 database ( P = 0.815).…”
Section: Discussionmentioning
confidence: 55%
“…Altogether 87 articles were selected for detailed evaluation, among which 24 articles were included (Figure 1). Generally, articles originated from Europe, 21‐36 Japan, 28,37‐41 the United States 42,43 and Oceania, 44 comprising 11 RCTs, 23,26,29,32,34,36,38,39,41,43,44 and 13 cohort or case‐control studies 21,22,24,25,27,28,30,31,33,35,37,40,42 . Most of the articles prescribed anti‐TNF‐α therapy, either with infliximab or adalimumab, with one article using vedolizumab.…”
Section: Resultsmentioning
confidence: 99%
“… 15 , 16 However, most studies have focused on the preventive effects of TNF-α inhibitors for POR. 17 , 18 Additionally, due to the concerns about immediate postoperative complications of TNF-α inhibitors, they are usually discontinued few weeks before elective surgery. 19 - 23 After discontinuing TNF-α inhibitors before surgery, the decision to restart or discontinue them depend on each clinician’s assessment, due to the lack of evidence.…”
Section: Introductionmentioning
confidence: 99%